In Vitro Effects of Polar Materials from Thermally Abused Frying Oil on Mammary Carcinoma Cell Migration (P05-004-19) - Joyce, Kaitlyn (Curr Dev Nutr, 2019)
OBJECTIVES: Widely consumed foods such as chicken, fish, and potatoes are regularly prepared by deep frying. The frying process involves temperatures exceeding 180 degrees Celsius and repeated frying cycles that result in thermally induced chemical changes of the oil's lipid structures. One such chemical change is an accumulation of polar compounds, including secondary lipid oxidation products, which are associated with several disease pathologies. Many European countries adhere to strict limits of less than 30% polar compounds within recycled fryer oils. There are no such regulations in the United States. Using a murine model of late-stage breast cancer (BC), we previously demonstrated an increased metastatic burden in mice consuming a diet of thermally abused frying oil (TAFO) compared with mice consuming fresh vegetable oil. To further understand this observation, we assessed 1) the amount of polar material in oil recycled for 300 minutes of deep frying, and 2) the effect the fractionated polar material from TAFO has on in vitro migration of 4T1 murine cancer cells. METHODS: We used silica column chromatography to separate the TAFO into polar and non-polar fractions. The polar fraction of TAFO (TAFO-PF) was retained from oil used to fry fish nuggets for a duration of 300 minutes. In vitro wound healing migration assays were conducted in the presence or absence of TAFO-PF in a concentration dependent manner. We assessed the wound closure rates (motility) of the highly metastatic 4T1 murine mammary carcinoma cell line. Live images were captured every hour for 24 hours to measure cell migration using brightfield microscopy. RESULTS: We found that after 300 minutes of frying, oil contained 74 ± 7.8 μg/mL of polar compound. 4T1 cells incubated over a period of 24 hours with diluted TAFO-PF achieved faster wound closure rates compared with cells incubated in growth media alone. CONCLUSIONS: Our results suggest that TAFO-PF increases motility as an indicator of the metastatic potential of BC cells. Ongoing work is being focused on conducting in vitro invasion assays on both 4T1 and human BC MDA-MB-231 cell lines in order to further understand the potential mechanisms and effects TAFO-PF has on cancer metastatic progression. FUNDING SOURCES: NIEHS Training (T32) Grant ES007326 Fellowship to JRH and ABO; UIUC Campus Research Board Beckman Grant and UIUC Hatch 1011659_ILLU-698-357.